Emissions assessment of a tanker in a chilean port using bi-directional cold ironing integrated to LNG. (August 2022) - Pérez Osses, Joel R.; Palma, Victor M.; Reusser, Carlos A.; Contreras, Jorge
Highlights: Relation between port vessel calls and quality of air in a specific port. A new energy management approach for a bi-directional cold ironing strategy. Bi-directional cold ironing strategy allows auxiliary engines work at their optimal point. Significant reduction can be achieved with this novel strategy. Abstract: Air pollution in coastal cities and nearby communities has become a health problem in the last decades because of the dispersion of pollutants produced by the various port activities. In this context, when a vessel at berth uses its auxiliary engines to generate the electric power to maintain its service, the operational profile is not continuous; the auxiliary engines work outside their fuel efficiency range, producing additional pollutant emissions. To reduce emissions while in port and at berth, two short-term options are considered: the first option is using alternative energy sources such as liquefied natural gas (LNG) instead of current fuels. The second option is using cold ironing technology, which enables to turn-off the vessels auxiliary engines, by feeding the services using shore power supply. In a classical cold ironing configuration, energy only flows from shore to on board. This work presents an emissions assessment of a tanker vessel at berth, applying a novel bi-directional energy flow strategy associated to a cold ironing system, integrating LNG, and compared to current fuels used, focused on the environmental impact on Quintero's Bay. This bay is one of the most important port areas of the Chilean coast deemed to be affected by emissions generated by intense port activities. Taking current fuels such as heavy fuel oil (HFO) and marine diesel oil (MDO) and ship's arrivals/departures from port as a reference case, the results presented in this work, show a significant reduction in emissions when applying the bi-directional energy flow strategy.